Route Planning Process by the Endangered Black Lion Tamarin in Different Environmental Contexts - Bufalo, Felipe [UNESP]; Kaisin, Olivier [UNESP]; de Almeida e Silva, Anne-Sophie [UNESP]; Amaral, Rodrigo Gonçalves [UNESP]; Messaoudi, Yness [UNESP]; Alcolea, Mirela [UNESP]; Zanette, Eduardo M. [UNESP]; Sabino, Gabriel Pavan; Börger, Luca; Culot, Laurence [UNESP] (Wiley, 2025)
Daily, primates take a variety of decisions to establish why, when, and where to move. However, little is known about the factors influencing and shaping primate daily routes. We investigated the decision-making processes linked to route planning in four groups of black lion tamarins (BLT—Leontopithecus chrysopygus). We studied these endangered platyrrhines within four distinct environmental contexts across their natural distribution (i.e., a continuous forest, a 500-ha forest fragment, a 100-ha forest fragment, and a riparian forest). We used the Change Point Test to identify the points of significant direction change (CPs), which can be considered travel goals along BLT daily trajectories and are key components of travel planning. Considering the high importance of fruits and gum in BLT's diet, we predicted that feeding trees would be the main factor shaping their paths (feeding CPs-FCPs). Also, given previous evidence that platyrrhines use landmarks (i.e., characteristic features from the terrain) as nodes in route network systems (i.e., points of intersection connecting habitual route segments), we expected part of CPs to be located close to the intersection points and to be associated with “locomotion” behavior (LCPs). Analyzing 61 daily paths in four forest fragments, our results showed that BLTs planned routes to reach feeding trees, which primarily determined path orientation. As hypothesized, locomotion was the most frequent behavior observed in CPs, but only in the continuous and riparian forests, with LCPs located as close to intersections as FCPs. Interestingly, these two areas presented the most extreme values (i.e., higher and lower values, respectively) in terms of used area, richness of resources and distances traveled between fruit-feeding trees. Our results suggest that BLTs plan daily routes conditional on the environmental context to reach travel goals, likely to maximize route efficiency to reach out of sight feeding trees.
Keywords: change point test; decision-making process; forest fragment; Leontopithecus chrysopygus; movement ecology; route networks